Notes for the constitutional interpretation of the Criminal Procedure Code - Burgos Mariños, Víctor (2011)
In the text of the New Criminal Procedure Code there are rule with inquisitive lags that have being applied literally, preventing the consolidation of the Accusatory Model in Peru. Such inquisitive lags affect the consolidation of the oral audiences system and the adversarial system of trial and the design of an efficient investigation based on the coordination between the police and the prosecution. The problem is aggravated because in Peru an integral reform of the legal system (Constitution and Organic Laws) to ensure real change in criminal justice was not carried out, as it was done in Chile and Colombia. Before the defect of the legislature, there is the option of a constitutional interpretation of these rules, as stipulated in Article X of TP the NCPP, to ensure the success of the criminal procedure reform in Peru.